ÙÙØ§ÙØ¶Ø© Ø§ÙØ¹ÙÙ Ø§ÙØ£Ø³Ø±Ù ÙÙØ±Ø¯Ø³ØªØ§Ù Ø§ÙØ¹Ø±Ù Ø£ÙÙÙØ°Ø¬Ø§ Ø¯Ø±Ø§Ø³Ø© ÙÙÙÙÙØ© ØªÙÙÙÙÙÙØ© - Arif, Arif Ali; Kholid, Ridwan Hazim (Al-Mawarid Jurnal Hukum Islam, 2015)
The following article tries to trace two important issues of act relating to domestic violence in Kurdistan, Iraq. This study denotes the study of contemporary jurisprudence regarding the issue of beating and coercion in the family. It sparked controversy in the perspective of the law and sharia law. This issue then be viewed from the concept of gender. The aim of this study is to clarify the concept of domestic violence and to indicate the issues contained in the legislation in jurisprudence viewpoint. Inductive approach used by researchers to collect scientific data in this research as well as analysis of other assistance. Results of this study have revealed that sometimes there are problems in the structure of the language, as well as contradict using of terminology. In addition, the lack of precision in the preparation draft of act which opposed to some provisions of sharia. This requires that the Kurdistan regional government to review the issue of requalification from the perspective of jurisprudence, law, languages, psychology and sociology. Keywords : Domesticviolence, Kurdistan, Gender, Kurdishlegislation.